2015
DOI: 10.1002/rcm.7366
|View full text |Cite
|
Sign up to set email alerts
|

Study of the non‐covalent interactions of ginsenosides and lysozyme using electrospray ionization mass spectrometry

Abstract: It has been demonstrated that ESI-MS is a powerful tool to probe the non-covalent interactions between lysozyme and ginsenosides. These results provide insights into the interaction of ginsenosides with lysozyme at the molecular level. The developed strategy could be applied to determine the interactions of proteins with other natural products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The relative signal intensities of all complexes increased first and then decreased with spray voltage (Figure ). Protein‐ligand complexes remained unchanged as the capillary voltage increases from 10 to 100 V, which further proved the specific interaction . The optimized CSI‐MS parameters referring to the spray voltage, capillary voltage, capillary temp, tube lens, and the distance were 2 kV, 40 V, 25 V, 250 V, and 6 mm, respectively, by maximizing the relative abundance of Aβ‐ginsenoside complexes ion.…”
Section: Resultsmentioning
confidence: 98%
“…The relative signal intensities of all complexes increased first and then decreased with spray voltage (Figure ). Protein‐ligand complexes remained unchanged as the capillary voltage increases from 10 to 100 V, which further proved the specific interaction . The optimized CSI‐MS parameters referring to the spray voltage, capillary voltage, capillary temp, tube lens, and the distance were 2 kV, 40 V, 25 V, 250 V, and 6 mm, respectively, by maximizing the relative abundance of Aβ‐ginsenoside complexes ion.…”
Section: Resultsmentioning
confidence: 98%
“…10,11 This striking property of lysozyme is an imperative feature for understanding the mechanism of transportation and metabolism of small molecules and drugs. 12,13 Studies of interactions of various natural products, such as juglone, 14 cinnamic acid, 15 naringin palmitate, 16 chelerythrine, 17 ginsenosides, 18 6-hydroxyflavone, 19 curcumin, 20 and sanguinarine, 21 with lysozyme have been found in the literature. Li et al have investigated the interaction of lysozyme with various dietary anti-oxidants and concluded that all of the studied compounds interacted very strongly with lysozyme, which may increase their half-life in vivo and lead to unwanted side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation on the labile interactions of proteins and ligands using electrospray ionization mass spectrometry combined with a mathematical method Dear Sir, Electrospray ionization mass spectrometry (ESI-MS) has become an essential tool to study the noncovalent interaction. A number of noncovalent complexes that could keep intact during the ESI process can be successfully determined by direct ESI experiments, such as enzyme-substrate complexes, [1,2] natural products-DNA complexes, [3,4] metal complexation with protein [5,6] and polyphenol-peptide. [7] Information such as stoichiometry, binding constants or reaction kinetics can be successfully obtained by ESI-MS.…”
mentioning
confidence: 99%
“…While the change of the capillary voltage would not affect the detection of the lysozyme-NAG 3 complex. [2] The mixtures of lysozyme, NAG 3 and various concentrations of rutin were determined firstly by ESI-MS. No complex of lysozyme with rutin was observed even though the molar ratio of ligandprotein increased to 40 : 1 (shown in Fig. S2).…”
mentioning
confidence: 99%
See 1 more Smart Citation